Polymeric Smart Coating Strategy for Titanium Implantsa. Issue 11 (1st April 2014) - Berts, Ida; Ossipov, Dmitri; Fragneto, Giovanna; Frisk, Andreas; Rennie, Adrian R.
<x xml:space="preserve">Abstract</x> Hydrogel coatings of modified hyaluronan on smooth titanium oxide surfaces that mimic orthopedics implant have been characterized using quartz crystal microbalance and neutron reflectivity measurements. Adsorption of bone morphogenetic protein‐2, BMP‐2, on a bare titanium oxide surface is compared to that on titanium oxide coated with hyaluronan with different chemical modifications, the most important being hyaluronan with bisphosphonate groups. Release of the BMP‐2 from these coatings was triggered by calcium ions. The amount of protein on the surface and the release both depend on the type of hyaluronan coating. We conclude that titanium oxide coated with bisphosphonate modified hyaluronan surfaces provides an excellent material for growth factor delivery.